Aplikasi Game Edukasi Tebak Gambar Solusi Pembelajaran Interaktif untuk Anak Usia - Dewi Mustari; Reko Syarif Hidayatullah; Retna Ningsih; Jumadi Jepri; Tri Yani Akhirina; Nani Muliyani Muliyani; Laksana Priyo Abadi; Ana Rusmardiana (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
This community service project aimed to develop an Android-based educational picture-guessing game as an interactive learning solution for early childhood, utilizing the Research and Development (R&D) method with the 4-D model (Define, Design, Develop, Disseminate). The application features a Linear Congruential Generator (LCG) for question randomization, visual content depicting animals, fruits, and everyday objects, a scoring system, and progressive difficulty levels designed to stimulate memory and cognitive skills in alignment with Piaget’s pre-operational stage theory. Validation by subject matter and media experts yielded high ratings, usability assessments met System Usability Scale (SUS) standards, and trials with young children demonstrated positive responses alongside improved object recognition from pre-test to post-test. The application offers a practical solution to the limitations of conventional learning methods and boosts learning motivation through visual and interactive elements.